2021
DOI: 10.1111/cei.13645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory findings in patients with leukocyte adhesion deficiency type I: A multicenter study in Turkey

Abstract: Leukocyte adhesion de ciency type I is rare primary immunode ciency disorder characterized by mutations in the ITGB2 gene encoding CD18. We present clinical and immunological features of 15 patients with leukocyte adhesion de ciency type I (LAD-I). Targeted next-generation sequencing was performed with either a primary immunode ciency gene panel comprising 266 genes or a small LADpanel consisting of ve genes for genetic analysis. To measure the expression level of integrins on the leukocyte surface, ow cytomet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…that were usually found pathogenic. Several novel mutations have also been reported earlier 6,11,[21][22][23] In a Chinese cohort of seven patients, novel mutations were identi ed in four 24 . Tipu et al 15 have reported genetic analysis of 12 Pakistani patients with ve pathogenic variants in eight of them and one of them was novel.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…that were usually found pathogenic. Several novel mutations have also been reported earlier 6,11,[21][22][23] In a Chinese cohort of seven patients, novel mutations were identi ed in four 24 . Tipu et al 15 have reported genetic analysis of 12 Pakistani patients with ve pathogenic variants in eight of them and one of them was novel.…”
Section: Discussionmentioning
confidence: 56%
“…As a result, there are recurrent infections, especially bacterial and fungal infections of varying severity, non-healing wounds without pus formation, and early death usually in infancy 3,8 . There is often a history of delayed separation of the umbilical cord and omphalitis 3,8,[11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…ITGB2 encodes the integrin beta chain, which combines with multiple different alpha chains to form different integrin heterodimers. It participates in cell surface-mediated signaling as well as immune response, and defects in this gene cause leukocyte adhesion deficiency ( 24 ). ITGB2 has also been reported to be negatively correlated with eGFR in patients with CKD ( 25 ) and involved in cell adhesion and extracellular matrix remodeling in renal cancer ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Dentro de los defectos de fagocitos se describe una enfermedad con incidencia aproximada de 1:100,000 nacidos vivos denominada deficiencia de adhesión leucocitaria (LAD, de "Leucocyte adhesion deficiency", por sus siglas en inglés), caracterizada por alteración en la migración de los leucocitos desde los vasos sanguíneos al sitio de inflamación, manifestándose clínicamente con retraso en la caída del cordón umbilical, onfalitis e infecciones bacterianas recurrentes de la piel y las mucosas, 3,4 además de leucocitosis persistente en la sangre periférica, debido a la incapacidad de los leucocitos para adherirse al endotelio vascular y migrar al tejido. 5,6 La deficiencia de adhesión leucocitaria se clasifica en tipo 1 (LAD-1), tipo 2 (LAD-2) y tipo 3 (LAD-3). La LAD-1 es un desorden autosómico recesivo provocado por mutaciones en el gen ITGβ2 que codifica para la cadena β (CD18) de las integrinas β2, esenciales para la adhesión de los leucocitos al endotelio vascular y la extravasación.…”
Section: Introductionunclassified
“…La mayor parte de los estudios asociados con deficiencia de adhesión leucocitaria provienen de países como India, Irán y Turquía, 5,6,11 y son escasos en Latinoamérica. [12][13][14] El primer caso en América del Sur fue reportado en 2012.…”
Section: Introductionunclassified